Placental interleukin-15 expression in recurrent miscarriage - Toth, Bettina; Haufe, Thomas; Scholz, Christoph; Kuhn, Christina; Friese, Klaus; Karamouti, Maria; Makrigiannakis, Antonis; Jeschke, Udo (American journal of reproductive immunology, 2010)
Citation Toth B, Haufe T, Scholz C, Kuhn C, Friese K, Karamouti M, Makrigiannakis A, Jeschke U. Placental Interleukin-15 expression in recurrent miscarriage. Am J Reprod Immunol 2010; 64: 402-410 Problem Cytokines play a fundamental role at the feto-maternal interface. A dysregulation of the cytokine profile could be linked with fetal rejection. This study investigated differences in the expression of the Th1 cytokine interleukin-15 (IL-15) of normal and disturbed pregnancy. Method of study Analysis of IL-15 expression by immunohistochemistry and real-time RT-PCR in placental tissue from normal pregnancies, spontaneous miscarriage and recurrent miscarriage (RM) was performed. Results Expression of IL-15 was upregulated on mRNA and protein level in the placenta of miscarriage patients, especially in patients with RM. Immunohistochemistry and immunofluorescence double staining revealed extravillous trophoblast cells (EVT) as IL-15-expressing cells. Staining results were confirmed by real-time PCR (TaqMan). Conclusion Increased expression of IL-15 in the decidua of patients with RM may be linked to disturbed implantation and vascularization with consecutive placental and fetal rejection.